The application of general self-consistent model on mechanical behaviour of fibre-reinforced cementitious composites. (15th August 2017) - Tian, H.; Cui, Y.H.; Zhang, Y.X.; Yang, C.
Highlights: Study of a new analytical model for FRCCs based on the general self-consistent method. Study of a hexagonal-shaped representative element model with multiple micro-cracks. Effective evaluation of the equivalent Young's modulus of a typical FRCC before and after cracking. Study of the effect of fibre orientation and the crack density of the matrix on Young's modulus of the FRCC. Abstract: Fibre-reinforced cementitious composite (FRCC), by adding short discrete fibres randomly in cementitious composites, exhibits substantially improved mechanical properties than conventional cementitious composites due to the fibre bridging action and the existence of multiple micro-cracks. In this paper, based on the general self-consistent method a new micromechanical analytical model is developed to model the material properties of the FRCCs. A hexagonal-shaped representative volume element model with multiple micro-cracks is established based on the microstructure of the FRCC to represent the transversely isotropic material characteristics. The developed model is used to evaluate the equivalent Young's modulus of a typical FRCC before and after cracking, and the results obtained are compared to those obtained from other analytical models and experimental data for validation. The influence of the aligned orientation of fibre and the crack density of the matrix on Young's modulus of the composite is also studied.